Pemeriksaan Pajak Sebagai Upaya Untuk Mendorong Kepatuhan Wajib Pajak - Antariksa Budileksmana (Journal of Accounting and Investment, 2001)
The role of taxation in financing the development of the country, as reflected in the State Budget (APBN) - today are becoming increasingly important. Under the self-assessment system, taxpayers are given full credence to calculate, pay and report tax obligations. As a logical consequence of such a system, the Directorate General of Taxation to make efforts to meet the expectations of the increasing role of taxes. One of them is the enforcement of the law (law enforcement) through the implementation of tax inspection, so that the process and the implementation of the system remain on the rules. With the Tax Examination will ensure compliance fulfillment of tax obligations in order to improve taxpayer compliance. The examination will be done to continue to improve the quality of examination and the examiners were there, along with the improvement of the applicable regulations. Of the taxpayer's own prosecuted and positive role that the inspection can be done effectively. With the tax audit allows obtaining feedback to improve understanding of the correct application of tax laws, which in turn will increase awareness to meet their tax obligations.